PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID PADA MATA PELAJARAN TEKNOLOGI JARINGAN KABEL DAN NIRKABEL KELAS XI TJKT SMK NEGERI 1 RANAH BATAHAN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Problems during learning at SMK N 1 Ranah Batahan still occur in the utilization of media, which is not yet optimal. Teachers only use Power Point with general and shallow material, making it difficult for students to understand. The lack of interactive media also makes students quickly bored, lose focus, and affects low Semester Exam results. The purpose of this study is to develop valid and practical Android-based learning media for the Cable and Wireless Technology Network subject in class XI TJKT at SMK Negeri 1 Ranah Batahan. The method used is Research and Development (R&D) with the ADDIE development model, which has several stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects as samples consisted of 1 teacher and 28 students. The data collection technique used questionnaires with a Likert scale. The results of this study showed that the average score of media validity test was 89.27% with a category of very valid, and material validity was 94.86% with a category of very valid. The practicality test of learning media for teacher responses reached 97.22% with a category of very practical, and for student responses reached 94.5% with a category of very practical. The conclusion based on this research is that Android-based learning media has been tested to be very valid and feasible, so it can be applied as a media for the learning process at school, particularly in class XI Computer Network and Telecommunication Engineering (TJKT).